2022
DOI: 10.3390/nano12152703
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Technics for Fabric/Fiber-Based Triboelectric Nanogenerators: From Yarns to Micro-Nanofibers

Abstract: Triboelectric nanogenerator (TENG), as a green energy harvesting technology, has aroused tremendous interest across many fields, such as wearable electronics, implanted electronic devices, and human-machine interfaces. Fabric and fiber-structured materials are excellent candidates for TENG materials due to their inherent flexibility, low cost, and high wearing comfort. Consequently, it is crucial to combine TENG with fabric/fiber materials to simultaneously leverage their mechanical energy harvesting and weara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Additionally, researchers have developed this PVDF-TrFE nanofiber into an intelligent gait sensing pad which can be used for personal gait judgment without power supply, showing a great potential in medical health detection (Figure 5D). Lee et al 107 108 lateral sliding mode, 109 single electrode mode, 110 and freestanding triboelectric layer mode 111 ), converting force signals into power signals (Figure 5E). 99 The vertical contact-separation mode sensors and lateral sliding mode sensors are typically composed of a pair of frictional layers with opposite polarity and two electrodes.…”
Section: Flexible Capacitive Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, researchers have developed this PVDF-TrFE nanofiber into an intelligent gait sensing pad which can be used for personal gait judgment without power supply, showing a great potential in medical health detection (Figure 5D). Lee et al 107 108 lateral sliding mode, 109 single electrode mode, 110 and freestanding triboelectric layer mode 111 ), converting force signals into power signals (Figure 5E). 99 The vertical contact-separation mode sensors and lateral sliding mode sensors are typically composed of a pair of frictional layers with opposite polarity and two electrodes.…”
Section: Flexible Capacitive Sensorsmentioning
confidence: 99%
“…The triboelectric sensors are novel devices proposed in recent years for energy harvesting and sensing purposes. They can operate in four basic modes (vertical contact-separation mode, lateral sliding mode, single electrode mode, and freestanding triboelectric layer mode), converting force signals into power signals (Figure E) . The vertical contact-separation mode sensors and lateral sliding mode sensors are typically composed of a pair of frictional layers with opposite polarity and two electrodes.…”
Section: Design Of Electrospun Flexible Biomechanical Sensorsmentioning
confidence: 99%
“…This high applied voltage during the electrospinning polarizes the dipole of PVDF. The spontaneous polarization further supports the electrical output of corresponding TENGs. Electrospinning is the least expensive way to fabricate consistent and continuous micro- or nanofibers. , Owing to its advantageous properties including flexibility, light weight, breathability, higher specific surface area, huge accumulated surface charge density, and porosity, micro- or nanofibers hold great promise for creating a new triboelectric active layer. , Compared to conventional techniques, the electrospinning technique may easily alter the dipole moment of specific polymers by organizing them molecularly or modifying their crystal array to achieve higher electrical outputs. Kim et al also found that the electrospun nanofibers tend to deliver enhanced power generation compared to casted films. The electrospun nanofiber’s network structure creates a greater surface area and higher roughness, which help to improve TENGs' electrical performance, whereas the casted film has a small and smoother uneven surface .…”
Section: Introductionmentioning
confidence: 99%
“…26−28 Electrospinning is the least expensive way to fabricate consistent and continuous microor nanofibers. 29,30 Owing to its advantageous properties including flexibility, light weight, breathability, higher specific surface area, huge accumulated surface charge density, and porosity, micro-or nanofibers hold great promise for creating a new triboelectric active layer. 31,32 Compared to conventional techniques, the electrospinning technique may easily alter the dipole moment of specific polymers by organizing them molecularly or modifying their crystal array to achieve higher electrical outputs.…”
Section: Introductionmentioning
confidence: 99%
“…T-TENGs can harvest large amounts of energy based on the movements of the human body in daily life, such as arm waving, walking, running, and arm and knee bending. [12][13][14][15] Previous studies have indicated that T-TENGs can be coated with polyvinylidene uoride (PVDF), PTFE, and polydimethylsiloxane (PDMS) to increase the frictional surface area. [16][17][18][19][20][21][22][23][24][25][26] Moreover, a high electrical output has been achieved using metals with hard properties as friction materials, for example, Au, Ag, and Cu.…”
Section: Introductionmentioning
confidence: 99%